The heart and the fist the education of a humanitarian, the making of a Navy SEAL - Greitens, Eric 1974-
The author describes how, after working as a humanitarian around the world, he realized that he could do nothing to stop violence or prevent people from becoming refugees and soon joined the elite Navy SEALs, where he drew on his humanitarian training as he battled injustice.